Remote Sensing Applications: Society and Environment - Remote Sensing Applications: Society and Environment (Elsevier, 2026)
The journal Remote Sensing Applications: Society and Environment (RSASE) is part of the Remote Sensing of Environment family of journals. It focuses on remote sensing studies that address specific topics with an emphasis on environmental and societal issues - regional / local studies with global significance.
FI 0.82
Q2
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Acuerdos transformativos; Transformative agreements; Cambio climático; Análisis geoespacial; Recursos naturales; Gestión ambiental; Riesgos naturales